The missing needle: Bibliographies, translation flows and retranslation - Paloposki Outi (Quasar, 2022)
Bibliographies are like haystacks: we engage in endless searches hunting for the needle we think must be there. Sometimes we find what we were looking for; other times, sifting through bibliographical data, all we come across is a lot of “unwanted” information. And yet perhaps we might, just once, turn the issue upside down? If for a moment we shift our gaze from what we are looking for (the needle) to instead consider our surroundings (the haystack), we may discover that the hay in itself is a source for new directions in research. Bibliographies may thus not only help us to solidify our understandingon our initial topic, they may also contextualise it and offer new avenues for research. The examples presented in this article deal with earlier work on specific topics in which bibliographies were initially used for locating statistical information. The problems encountered in the course of these searches ultimately led the scholar to pose new questions. An attempt to survey translation flows led to studies on personal agency or ideological or market pressures, and the search for retranslated literature turned into a study of categorization and classification problems when defining the object, retranslations – which, for its part, engendered a study of revision. Thus, while learning to cope with inaccurate or even misleading sources, we may also learn to see wider implications of the issue in question.
Translating Scandinavia : Scandinavian Literature in Italian and German Translation, 1918-1945